(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2023)
Jatropha multifida L. is a plant traditionally recognized for its medicinal properties. This plant has been reported to possess anti-microbial, anti-oxidative, wound healing and anti-inflammatory properties. The study aimed to evaluate the anti-diabetic potentials of J. multifida. The study deals with the extraction of the leaves of the plant by using 50% ethanol followed by fractionation of the ethanol extract obtained. Various physicochemical parameters and phytochemical analyses were done by TLC and HPTLC. Phytochemical analysis of the extract and its fraction indicated high concentrations of flavonoids, phenolic acid and saponins. The effects of the 50% ethanol extract of J. multifida leaves, and its hexane fraction were investigated in high-fat diet and Streptozotocin-induced diabetic rats. At the end of the treatment, the reduction in blood glucose level in rats treated with ethanol extract at a dose of 400 mg/kg was found to be 117.5±1.7 and hexane fraction at 200 mg/kg was found to be 105±2.5. A significant improvement in lipid profile and liver abnormalities of the rats was observed. The result of the present study is also justified by histopathological examinations of the pancreas and liver. Therefore, the current study proved that both the ethanolic extract of J. multifida and its hexane fraction possess bioactive constituents that could be responsible for the anti-diabetic properties. Out of the two, maximum improvement was seen using hexane fraction at 200 mg/kg. This may be due to the active phytoconstituents isolated from the fraction of the 50% ethanolic extract of the leaves.